Burkina Faso : Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Extension of the Arrangement, Modification of Continuous Performance Criterion, and Rephasing of Disbursement-Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Burkina Faso's Sixth Review Under the Three-Year Arrangement under the Extended Credit Facility and Requests for Extension of the Arrangement, Modification of Continuous Performance Criterion, and Rephasing of Disbursement. Domestic revenue collection over performed by a significant margin in 2012, and program performance remains good. In 2012, domestic revenues were higher than targeted by 1.7 percentage points of revised GDP. Lower financing needs resulted in government savings in the banking system. The authorities are prioritizing improvements in public investment planning, spending capacity to meet infrastructure, and training needs that constrain growth.